Efficacy of avapritinib versus best available therapy in the treatment of advanced systemic mastocytosis: myelodysplastic syndrome - Reiter, Andreas; Gotlib, Jason; Álvarez-Twose, Iván; Radia, Deepti H.; Lübke, Johannes; Bobbili, Priyanka J.; Wang, Aolin; Norregaard, Chelsea; Dimitrijevic, Saša; Sullivan, Erin; Louie-Gao, Melinda; Schwaab, Juliana; et al. (Leukemia, 2022)
Advanced systemic mastocytosis (AdvSM) is a rare myeloid neoplasm associated with poor overall survival (OS). This study (NCT04695431) compared clinical outcomes between patients with AdvSM treated with avapritinib in the Phase 1 EXPLORER (NCT0256198) and Phase 2 PATHFINDER (NCT03580655) trials (N = 176) and patients treated with best available therapy (BAT; N = 141). A multi-center, observational, retrospective chart review study was conducted at six study sites (four European, two American) to collect data from patients with AdvSM who received BAT; these data were pooled with data from EXPLORER and PATHFINDER. Comparisons between outcomes of OS, duration of treatment (DOT), and maximum reduction in serum tryptase were conducted between the treatment cohorts, with adjustment for key covariates. The results indicated that the avapritinib cohort had significantly better survival (adjusted hazard ratio (HR) (95% confidence interval (CI)): 0.48 (0.29, 0.79); p = 0.004) and significantly longer DOT (HR: 0.36 (0.26, 0.51); p < 0.001) compared to the BAT cohort. Additionally, the mean difference in percentage maximum reduction in serum tryptase levels was 60.3% greater in the avapritinib cohort (95% CI: −72.8, −47.9; p < 0.001). With no randomized controlled trials comparing avapritinib to BAT, these data offer crucial insights into the improved efficacy of avapritinib for the treatment of AdvSM.
Gesehen am 31.10.2023